2021
DOI: 10.1002/cssc.202002756
|View full text |Cite
|
Sign up to set email alerts
|

Control of Molecular Catalysts for Oxygen Reduction by Variation of pH and Functional Groups

Abstract: In the search for replacement of the platinum‐based catalysts for fuel cells, MN4 molecular catalysts based on abundant transition metals play a crucial role in modeling and investigation of the influence of the environment near the active site in platinum‐group metal‐free (PGM‐free) oxygen reduction reaction (ORR) catalysts. To understand how the ORR activity of molecular catalysts can be controlled by the active site structure through modification by the pH and substituent functional groups, the change of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…During the past years, we have shown the great importance of the interaction between molecular catalysts and their support material and found that BP2000 is most suitable for macrocyclic compounds due to its high surface area and average pore size, which promotes cooperativity between catalytic sites, resulting in increased selectivity and lower ORR overpotential. Herein, we present our study of ORR catalytic performance and durability under alkaline conditions using four different substituted iron phthalocyanines supported on BP2000. The results show that iron­(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadeca (fluoro)­phthalocyanine (FeFPc) (Figure ) adsorbed on BP2000 (FeFPc@BP2000) has the highest catalytic activity of the four FePCs, higher than that described recently by others who used carbon nanotubes as the support, making it one of the best molecular catalyst–support system reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…During the past years, we have shown the great importance of the interaction between molecular catalysts and their support material and found that BP2000 is most suitable for macrocyclic compounds due to its high surface area and average pore size, which promotes cooperativity between catalytic sites, resulting in increased selectivity and lower ORR overpotential. Herein, we present our study of ORR catalytic performance and durability under alkaline conditions using four different substituted iron phthalocyanines supported on BP2000. The results show that iron­(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadeca (fluoro)­phthalocyanine (FeFPc) (Figure ) adsorbed on BP2000 (FeFPc@BP2000) has the highest catalytic activity of the four FePCs, higher than that described recently by others who used carbon nanotubes as the support, making it one of the best molecular catalyst–support system reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Stability tests of corrole 1 @C800 show gradual loss of activity: 29 % of the starting HzOR current density are lost after 50 cycles (Figure 9e). On other N 4 macrocycles, this could arise from demetallation, especially since loss of iron is promoted by nitrogen protonation due to the high local proton concentration generated by the HzOR [66] . However, corroles are typically very stable towards hydrolysis [45,44] .…”
Section: Resultsmentioning
confidence: 99%
“…On other N 4 macrocycles, this could arise from demetallation, especially since loss of iron is promoted by nitrogen protonation due to the high local proton concentration generated by the HzOR. [66] However, corroles are typically very stable towards hydrolysis. [45,44] Alternatively, the iron center could be deactivated by the formation of inactive Fe IV -O-Fe IV dimers, due to the alkaline and oxidizing environment of the HzOR.…”
Section: Resultsmentioning
confidence: 99%
“…This result evidenced the importance of the corrole dimensions on the ORR catalytic activity and led the researchers to [45][46][47] look to novel corrole-bearing substituents that can influence both the electronic and size-related properties of catalysts. In particular, the -CF 3 group as the meso-substituent attracted some attention because it is a small and strong electronwithdrawing substituent, two features that are particularly promising for the target application.…”
Section: Oxygen Reduction Reaction (Orr)mentioning
confidence: 98%
“…To further detail the different parameters that govern the ORR process, the influences of pH and peripheral substituents were studied via the comparison of the catalytic behavior of three Co corrole complexes (Fig. 12a-c), 46 with the support of DFT calculations.…”
Section: Oxygen Reduction Reaction (Orr)mentioning
confidence: 99%